Arrival of a new anuran invader in Borneo: First record of Microhyla heymonsi Vogt, 1911, from Sabah (Amphibia, Microhylidae) - Quah, Evan Seng Huat; Aderina Dukit; Alvinus Joseph; Paul Y. Imbun (Pensoft Publishers Ltd., 2025)
Microhyla heymonsi Vogt, 1911 is a wide-ranging commensal species of frog which is currently re‑ported from Taiwan, China, Vietnam, Laos, Thailand, Myanmar, Peninsular Malaysia, Singapore, and Sumatra. During a recent scientific expedition in Tuaran District, Sabah, Borneo, several specimens were collected and identified as M. heymonsi based on morphological characters. This represents a new locality record and the first report of M. heymonsi in Borneo. The presence of this species in Borneo is likely due to accidental human transport, and there is potential for its spread across Borneo due to its high adaptability to human-modified landscapes.